Case report: Brucellosis with rare multiple pulmonary nodules in a depressed patient - Zhou, Mingjing; Wang, Ke; Liu, Haoyuan; Ran, Ran; Wang, Xuan; Yang, Yuqian; Han, Qunying; Zhou, Yi; Liu, Xiaojing (Frontiers in Medicine, 2023)
Background Brucellosis is a zoonotic disease that threatens public health and creates an economic burden. Unfortunately, it is often overlooked in developing countries, with misdiagnosis causing negative impacts on those with low income. Although the symptoms of brucellosis are commonly reported as fever and fatigue, rare pulmonary, and psychiatric involvements should also be considered. We present the first brucellosis patient in China with multiple pulmonary nodules and depression. Furthermore, this report highlights the importance of collecting patient history in epidemic areas of brucellosis. Case presentation We report the case of a 40-year-old woman with intermittent fever for 2 months and gradually accompanied by chills, dry cough, arthralgia, and fatigue. The patient was also diagnosed with depression after fever. She received symptomatic treatment at a regional hospital; however, there was no significant symptom relief. She suddenly developed hemoptysis 1 day prior to arrival at our hospital, where we discovered that her liver, spleen, neck, and axillary lymph nodes were enlarged, and there were multiple nodules in both lungs. The patient was eventually diagnosed with brucellosis after the serum agglutination test and received antibiotic therapy, which provided symptom relief. Conclusion This report describes a case of brucellosis with uncommon multipulmonary nodules and depression in China. This study has widened the evidence of respiratory involvement due to brucellosis. Second, it demonstrates the importance of collecting a comprehensive medical history, especially in epidemic areas. In conclusion, for febrile patients with pulmonary nodules and depression, especially in endemic areas, brucellosis should be considered.